The Psychometric Properties of the Norwegian version of Children’s Yale-Brown Obsessive Compulsive Scale (CY-BOCS) - Kornør, Hege; Skarphedinsson, Gudmundur (PsykTestBarn, 2013)
Description: Children’s Yale-Brown Obsessive Compulsive Scale (CY-BOCS) is a semi-structured interview developed to assess symptoms of obsessive-compulsive disorder (OCD) in children and adolescents. The instrument has a total scale and two subscales for obsession and compulsion, respectively. A clinician interviews the child and parents, and scores the answers. Wayne K. Goodman and colleagues developed the instrument, which was published in 1997. Pål Zeiner and Robert Valderhaug have made separate translations of CY-BOCS. It is unclear who holds the copyright to the instrument. Literature search: We included one study with one Norwegian (n=28) and one Swedish (n=40) sample, and one study with two Swedish samples (n=121+113). All participants were children and adolescents referred to or in treatment for OCD. The studies reported mean scores and correlations between CY-BOCS scores and scores from the Child OCD Impact Scale (COIS) and Child Behavior Checklist (CBCL), respectively. None of the studies reported measures of reliability or criterion validity. Psychometrics: Correlations between CY-BOCS scores and COIS parent- and self-report were Spearman’s rho 0.36 and 0.61, respectively. Conclusion: The construct validity of Norwegian CY-BOCS scores has little empirical support due to inconsistent correlation coefficients based on small sample data. The lack of further evidence for the psychometric properties of the Norwegian version of CY-BOCS dictates that clinicians should carry out great caution in interpreting scores. Psychometric research is needed, with special focus on inter-rater reliability and criterion validity.